The effect of peer relationship on subjective well-being among Chinese middle school students: a chain mediation model - Wang, Lijun; Xiang, Weiqin; Yang, Ziyi; Cheng, Mengfei; Shi, Jingyi; Wan, Zhendong (Frontiers in Psychology, 2025)
ObjectiveTo explore how peer relationship relates to subjective well-being in Chinese adolescents, and to examine the mediating roles of dispositional optimism and two emotion-regulation strategies (cognitive reappraisal, expressive suppression).MethodsA total of 1897 middle school students aged 11–19 (14.86 ± 1.69, 51.3% males) from Anhui Province, China, completed four questionnaires, by using a cluster convenience sampling method. The Adolescent Peer Relationship Scale, Index of Well-being, Emotion Regulation Questionnaire, and the Life Orientation Test-Revised were used to assess peer relationship, subjective well-being, emotion regulation ability and dispositional optimism, respectively. Data were statistically analyzed using descriptive statistics, correlation analysis, group comparisons, and mediation analysis.ResultsPeer relationship significantly and positively predicted the subjective well-being of middle school students (β = −0.339, p < 0.001). Dispositional optimism (β = −0.391, p < 0.001) and cognitive reappraisal (β = −0.161, p < 0.001) were both found to partially mediate this relationship. Specifically, dispositional optimism significantly predicted both cognitive reappraisal (β = 0.242, p < 0.001) and subjective well-being (β = 0.260, p < 0.001), and cognitive reappraisal also positively predicted subjective well-being (β = 0.191, p < 0.001). Mediation analysis revealed that both dispositional optimism and cognitive reappraisal significantly mediated the relationship between peer relationship and subjective well-being. The mediating effect included three distinct paths: (1) the independent mediating effect of dispositional optimism (effect = −0.489), (2) the independent mediating effect of cognitive reappraisal (effect = −0.149), and (3) the chain mediating effect of dispositional optimism and cognitive reappraisal (effect = −0.087).ConclusionThis study found that peer relationship is positively associated with subjective well-being of middle school students. Furthermore, this relationship is explained through two key mechanisms: the independent mediating roles of dispositional optimism and cognitive reappraisal, and the sequential mediation pathway involving both. These findings underscore the importance of fostering positive peer relationship and cultivating psychological strengths such as optimism and adaptive emotion regulation strategies to enhance adolescents’ well-being.